Meningkatkan Produktivitas Karyawan: Peran Kompensasi, Disiplin Kerja dan Gaya Kepemimpinan di PT Usaha Gunabhakti Mandiri - Putra, Rudi Eko; Mudjijah, Slamet (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research aims to analyze the influence of compensation, work discipline and leadership style on employee productivity at PT Usaha Gunabhakti Mandiri. The method used in this research is a survey method with the sample size determined based on calculations using the Slovin Formula. The data collection technique is carried out through distributing questionnaires that have passed validity and reliability tests to ensure the accuracy and consistency of the data obtained. Data analysis in this research was carried out using the SPSS Version 27 application, which includes a series of statistical tests such as validity tests, reliability tests, correlation tests, multiple linear regression tests, and classic assumption tests to identify the relationship and influence between the variables studied. The results of this research indicate that compensation, work discipline, and leadership style have a significant influence simultaneously on employee productivity. The coefficient of determination obtained indicates that most of the variation in employee productivity can be explained by these three factors, while the remainder is influenced by other factors that are outside the scope of this research. Based on these findings, this research recommends improvements in aspects of compensation, work discipline and leadership style in order to better support optimal and sustainable increases in employee productivity in the future.